(untitled) (Research, Society and Development, 2021)
This article seeks to analyze networking in the district of Sussundenga, based on its social dynamics, seeking to highlight the main actors and their relationship in the context of the implementation of programs and actions aimed at preventing and combating child malnutrition in Mozambique. This is a cross-sectional, descriptive study, with a qualitative approach, which used systematic observation and semi-structured interviews applied to managers in different areas, to the local producer, as well as to women in the communities. Governmental and non-governmental organizations have contributed to the various programs and actions, especially regarding social security and food and nutrition security. However, the weak community involvement, above all, of women, partly due to difficulties of a logistical nature, of articulation and institutional coordination, may be jeopardizing the effectiveness in its implementation. Considering that these women exchange a variety of information related to eating practices with other women in their local network, this situation could be seen as an opportunity for their greater insertion and visibility in networking aimed at nutrition, combined with their experiences and perspectives of intervention suitable for context of an integrated approach. Thus, it is believed that networking with effective and egalitarian community involvement, coupled with the location preferably as close as possible to the sector responsible for coordinating actions and programs in the territory where they are implemented, may be important in the results of prevention and combat child malnutrition, as well as for reframing and social mobilization in relation to the role of women in local development processes.